A nitrogen rich polymer as an organo-catalyst for cycloaddition of CO2 to epoxides and its application for the synthesis of polyurethane. Issue 7 (15th August 2017) - Verma, Shailesh; Kumar, Gaurav; Ansari, Amamudin; Kureshy, Rukhsana I.; Khan, Noor-ul H.
Abstract : A nitrogen-rich cyanuric–urea polymer (CUP ) was synthesized in a single step under solvent free conditions. Abstract : A nitrogen-rich cyanuric–urea polymer (CUP ) was synthesized in a single step under solvent free conditions. The catalyst was characterized by microanalysis, FT-IR, XRD, 13 C/ 15 N CP-MAS NMR, SEM, TEM, EDX spectroscopy, nitrogen sorption–desorption studies and CO2 TPD. TheCUP was used as an efficient catalyst for the cycloaddition reaction of epoxides with CO2 under solvent and additive free conditions. The product cyclic carbonates were obtained with high conversion and excellent selectivity. This method also provides a straightforward approach with great application to access polyurethane/polyhydroxyurethane in a single step with good yield.